Analyzing Transportation Safety: The Role of Signage in Preventing Accidents: The Role of Signage in Preventing Accidents - Dewi, Tria Ratna (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This article explores the critical role of signage in enhancing transportation safety and preventing accidents on roadways. Effective signage serves as a vital communication tool that informs drivers and pedestrians of regulations, hazards, and navigational guidance. Through a comprehensive analysis of existing literature and case studies, we examine how various factors—such as visibility, clarity, design, and positioning of signage—contribute to overall road safety. The article highlights the correlation between well-designed signage and a significant reduction in traffic incidents, particularly in high-risk areas. Furthermore, we discuss the psychological impact of signage on driver behavior and decision-making processes, emphasizing how clear and intuitive signage can lead to safer driving habits.The study also considers the role of technological advancements, such as digital and interactive signage, in enhancing the effectiveness of communication on the roads. By identifying the key elements that influence the effectiveness of transportation signage, this research aims to provide actionable insights for policymakers, urban planners, and transportation safety advocates to improve road safety measures. Recommendations for best practices in signage design and implementation are presented, along with case studies illustrating successful interventions. A quantitative approach was used using a Likert scale questionnaire to collect drivers' perceptions regarding safety regarding signage (traffic signs). This questionnaire focuses on identifying areas that frequently experience accidents, congestion and certain safety problems. A Likert scale was used to assess the level of satisfaction and perception regarding safety along the road. The research surveyed a total of 116 respondents who were residents of the city of Tegal.